2019
DOI: 10.1080/10640266.2019.1663478
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating measures validated in pregnancy samples: a systematic review

Abstract: Although disordered eating in pregnancy has been linked to numerous negative consequences, there is currently no published instrument specifically devised to identify or measure such symptoms in pregnancy. As such, this study systematically reviewed the literature to evaluate the performance of general measures of disordered eating in pregnancy samples. A systematic search of the following electronic databases was undertaken from inception to April 2019: Scopus, Medline, PsycINFO, Embase, ProQuest Dissertation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Our three studies utilized different screening approaches for EDs in antenatal samples in Germany and the UK: the general ED questionnaire EAT‐8 (Richter et al, 2016) via online dissemination in an unselected sample (Study 1), a modified‐SCOFF (Morgan et al, 1999; Study 2) and self‐reported ED history (Study 3) in preselected samples with elevated scores on other screeners for mental health burden (Howard et al, 2018; Mueller et al, 2020). Our findings align with recent aggregated evidence (Bannatyne et al, 2021) and confirm that there are no available screening instruments that can be recommended for antenatal samples. Related to screening pregnant women for previous EDs, the options based on validated instruments are limited as most focus on current symptoms (Lindvall Dahlgren & Wisting, 2016; Schaefer et al, 2021), which is especially important to consider given that most women will experience a temporary remission during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our three studies utilized different screening approaches for EDs in antenatal samples in Germany and the UK: the general ED questionnaire EAT‐8 (Richter et al, 2016) via online dissemination in an unselected sample (Study 1), a modified‐SCOFF (Morgan et al, 1999; Study 2) and self‐reported ED history (Study 3) in preselected samples with elevated scores on other screeners for mental health burden (Howard et al, 2018; Mueller et al, 2020). Our findings align with recent aggregated evidence (Bannatyne et al, 2021) and confirm that there are no available screening instruments that can be recommended for antenatal samples. Related to screening pregnant women for previous EDs, the options based on validated instruments are limited as most focus on current symptoms (Lindvall Dahlgren & Wisting, 2016; Schaefer et al, 2021), which is especially important to consider given that most women will experience a temporary remission during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Much research has focused on screening for depression in pregnant women (Howard et al, 2018; O'Connor et al, 2016), whereas little attention has been paid to identifying eating disorders (EDs) in pregnancy. The prevalence of EDs during pregnancy ranges between 1.5% and 7.6% (Bye et al, 2020; Easter et al, 2013; Watson et al, 2013), with discrepancies largely attributable to differences in psychometric instruments employed and operationalized diagnostic criteria (Bannatyne et al, 2021; Bye et al, 2018). The prevalence of EDs has been estimated to be around 15% in pregnant women by a recent review (Bye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These disparities could be explained by the diversity of assessment tools, varying from self-reported questionnaires (based on adapted versions of pre-existing scales for eating disorders, or designed on items derived from the DSM-4 or DSM-5 criteria) to structured interviews 9 , hence emphasizing the need for an international consensual and accurate pregnancy-speci c screening tool, as previously suggested by a Delphi study 19 , to make comparisons easier in research, and to minimize the probability of false negative and false positive tests. On top of that, a recent systematic review refuted the suitability of the traditional existing measures for evaluating eating disorders in pregnancy, pointing out that among sixteen scales applied across countries, not more than four were presented along with documented psychometric characteristics, yet none was able to stand up for a meritorious level of clinical pertinence (in terms of psychometric performance as internal consistency, criterion-related validity, screening accuracy…) to the point of being set as a "gold standard" measure or substituting the need for a speci cally conceived instrument for identifying dysfunctional eating symptoms during pregnancy 20 .…”
Section: Introductionmentioning
confidence: 99%